Tribute to Lois Ehrenburg at Jon Jon's - Watkins, Howard::::::::: (1981)
Bruce Bronzan embracing Lois Ehrenburg as he gives her proclamation; Karen Humphrey, Dale Doig, Mary Nelson, Jim O'Banion clapping